ANALISIS DAYA TAMPUNG SEKOLAH MENENGAH BERDASARKAN DATA PERTUMBUHAN PENDUDUK TAHUN 2011-2020 DI KECAMATAN SAMBAS - Halina, Halina; Buwono, Sri; Harjanti, Diah Trismi (Universitas Tanjungpura, 2022)
In 2020, Sambas will have 52.538 people and 13 school units. Every year the population in Sambas District is always increasing, which can cause an imbalance in the population with the availability of facilities. This research aims to (1) Find out the capacity of secondary schools for the opportunity to school for residents in Sambas, (2) Find out the rate of population growth, (3) Find out the factor that affects population growth, and (4) Find out the population in 2030. This research used descriptive quantitative approach methods. The research data source used is public documentation obtained from government agencies. Overall, educational facilities in Sambas District can accommodate the entire school-age population regarding the number of schools, the number of teachers, and the number of classes. The opportunity for the community to obtain education in Sambas is indicated by the Gross Enrollment Rate (GER) indicator of 165.6% and Net Enrollment Rate (NER) of 95,9%. Population growth in Sambas has a medium classification level with a growth rate of 1,72%. Population growth in Sambas is influenced by the birth factor, which has increased by 42.6% in ten years. In 2030, the population is estimated as 62,420 people, with a secondary school age of 2,236 people. Overall, the educational facilities available today can accommodate the entire population ten years later.